2022
DOI: 10.1371/journal.pone.0264371
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing COVID-19 vaccine uptake among adults in Nigeria

Abstract: Background Emerging variants of Coronavirus disease 2019 (COVID-19) has claimed over 3000 lives in Nigeria and vaccination remains a means of reducing the death toll. Despite ongoing efforts by the government to ensure COVID-19 vaccination of most residents to attain herd immunity, myths and beliefs have adversely shaped the perception of most Nigerians, challenging the uptake of COVID-19 vaccine. This study aimed to assess the factors influencing the awareness, perception, and willingness to receive COVID-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
47
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 27 publications
7
47
2
Order By: Relevance
“…The main reason for not having had a COVID-19 vaccine, or for being unsure of whether to have a vaccine, was related to concerns about possible side effects of the vaccine. This finding is in line with international [ 35 ], regional African [ 36 ] and local South African [ 17 , 23 ] studies conducted since the roll-out of COVID-19 vaccine programmes. Even while COVID-19 vaccines were still under development, fear of possible side effects was cited as a key reason for not having a vaccine once it became available [ 13 , 14 , 37 ], indicating that risk perception is a major barrier to uptake of COVID-19 vaccination.…”
Section: Discussionsupporting
confidence: 87%
“…The main reason for not having had a COVID-19 vaccine, or for being unsure of whether to have a vaccine, was related to concerns about possible side effects of the vaccine. This finding is in line with international [ 35 ], regional African [ 36 ] and local South African [ 17 , 23 ] studies conducted since the roll-out of COVID-19 vaccine programmes. Even while COVID-19 vaccines were still under development, fear of possible side effects was cited as a key reason for not having a vaccine once it became available [ 13 , 14 , 37 ], indicating that risk perception is a major barrier to uptake of COVID-19 vaccination.…”
Section: Discussionsupporting
confidence: 87%
“…This may be due to the fear of getting the disease again and thus more intention to vaccine uptake. Our finding was in line with the findings of a study conducted among adults in Nigeria, which showed that individuals without prior diagnosis of COVID-19 had less perception to receive COVID-19 vaccine (adjusted OR = 0.59 (95% CI: 0.38-0.92), P = 0.021) than those that were previously COVID-19 positive [39].…”
Section: Discussionsupporting
confidence: 91%
“…Nigerian participants were more likely to prefer appeals related to social norms with both healthcare provider and peer messengers. This demonstrates that social norms may be powerful influences for improving vaccine uptake in Nigeria, suggesting that identifying individuals that are perceived as peers, rather than hierarchical, may be useful for vaccine promotion [ 33 ].…”
Section: Discussionmentioning
confidence: 99%